IMPROVING THE STRATEGY OF INTERACTION BETWEEN THE STATE AND SMALL BUSINESSES IN KAZAKHSTAN - Dyusembaeva L.K; Bulakbay Zh.М; Babazhanova Zh.А; Nurbayeva G.Ye (Academic Journal of Physical and Chemical Sciences, 2019)
Forming effective innovation mechanisms in the economy of Kazakhstan using the potential of small business is a pressing problem and the fact that the accumulated experience of industrialized and post-industrial countries focused on the development of market economy relations certainly shows that small business is a necessary condition for achieving economic success and is the main engine of innovation development. All structures are interested in the development of such a sector of the economy, since small business is the basis on which the entire economic pyramid will be created, which can provide jobs for a significant part of the population and form the middle class of society. From this it follows that the faster a significant stratum of small business entities is created within the state, the more actively the model of an effective market economy will develop, including the implementation of the tasks of economic restructuring and transition to a new level of technological structure.